Preface - Mohd. Noor, Faridah Noor (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2017)
In the years to come, the issue on sustainability will be of a major concern. Humans plough the earth of her resources for the betterment of mankind. At times, not a moment’s thought is given to consider the the repercussions from a single plundering action. The key to sustainability is not to break the cycle of harmonious coexistence with our natural environment. Such action is to ensure that our future generations will have the same opportunity the benefits as we do today. In fact, the present generation need to start recovering what has been lost in order to leave behind something worthy for the future generation to remember us for.